Dimensi Keperawatan Ibu Hamil pada Keluarga Hindu di Bali - Bhandesa, Asthadi Mahendra (Jurnal Kajian Bali (Journal of Bali Studies), 2021)
Balinese Hindu families treat pregnant mothers carefully by fulfilling not only their needs biologically, psychosocially, socially, but also spiritually. This research aims to clarify the perspective of nursing care for pregnancy in Balinese Hindu families. Data were collected through observation and in-depth interviews and analyzed by ethnomedicine theory. The findings were: Firstly, in biological care, taking care of pregnancy needs in healthy food and beverage consumption, breathing and sleep management. Secondly, in psychological care, healthy life was well maintained by good thinking, speaking, and doing, and giving special attention, especially in the first and third trimesters. Thirdly, good communication and a stable and well-maintained mood of the pregnant mother as social care. Lastly, the spiritual care through spiritual ceremonies, such as melukat , 7 th -month ceremony, praying, listening to gayatri mantram, and some holy kidung . It concludes that nursing care in Balinese Hinduism families is in line with national medical care.